2022
DOI: 10.3390/plants11091100
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic Stresses in Plants and Their Markers: A Practice View of Plant Stress Responses and Programmed Cell Death Mechanisms

Abstract: Understanding how plants cope with stress and the intricate mechanisms thereby used to adapt and survive environmental imbalances comprise one of the most powerful tools for modern agriculture. Interdisciplinary studies suggest that knowledge in how plants perceive, transduce and respond to abiotic stresses are a meaningful way to design engineered crops since the manipulation of basic characteristics leads to physiological remodeling for plant adaption to different environments. Herein, we discussed the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 157 publications
0
16
0
Order By: Relevance
“…Stresses caused by drought, heat, cold, and salt all induce an increase in the quantity of Ca 2+ (signal molecules) that enters the cytoplasm of the cell from either its own reserves or an apoplastic source. One form of sensor for the stress signals is thought to be the passages that govern Ca 2+ entrance ( Aftab et al, 2021 ; Javaid et al, 2022 ; Paes de Melo et al, 2022 ). Other than Ca 2+ , ROS and nitric oxide (NO) are other messenger molecules involved in inducing plant response to cold stress.…”
Section: Plant Mechanisms For Sensing and Response To Abiotic Stressmentioning
confidence: 99%
“…Stresses caused by drought, heat, cold, and salt all induce an increase in the quantity of Ca 2+ (signal molecules) that enters the cytoplasm of the cell from either its own reserves or an apoplastic source. One form of sensor for the stress signals is thought to be the passages that govern Ca 2+ entrance ( Aftab et al, 2021 ; Javaid et al, 2022 ; Paes de Melo et al, 2022 ). Other than Ca 2+ , ROS and nitric oxide (NO) are other messenger molecules involved in inducing plant response to cold stress.…”
Section: Plant Mechanisms For Sensing and Response To Abiotic Stressmentioning
confidence: 99%
“…Further, the more pronounced degree of differences in the chemical composition of bark than wood suggests that the bark is more sensitive to the environment than the wood. More specifically, changes in the contents of the cellulose, lignin and substances soluble in EtOH of bark of trees growing under three environmental stresses revealed that trees adopt certain physiological mechanisms to cope with the abiotic stresses [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plants have developed several biochemical, physiological, and metabolic responses to withstand environmental stress factors. Understanding plants’ molecular, cellular, physiological, and biochemical changes during abiotic stresses is crucial for better crop management [ 16 , 19 , 20 ]. Plants have primary and secondary stress response mechanisms to protect themselves from various abiotic stresses.…”
Section: General Effects Of Drought Heat and Salt Stress On Plant Gro...mentioning
confidence: 99%
“…Therefore, integrating multi-omics data within the context of systems biology can provide more profound knowledge for future directions (molecular biology, genome editing, etc.) [ 15 , 16 , 17 ]. In this review, we discussed the recent advancements in functional genomics, transcriptomic, and proteomic analyses to understand the adaptation and tolerance mechanisms enhancing drought, extreme temperature, and salinity in different cereal crops.…”
Section: Introductionmentioning
confidence: 99%